Peran Duta Wisata di Kabupaten Kutai Kartanegara: (Studi Kasus dalam Kegiatan Sosialisasi Sadar Wisata pada Siswa SMA) - Achmad Fahreza (UNISBA Press, 2023)
Abstract. As an archipelago that has a lot of diversity, Indonesia has diverse characteristics. However, awareness of the tourism sector in Indonesia is still not fully massive, lack of enthusiasm from the community underlies the lack of concern for the potential of Indonesia through this tourism phenomenon. Including in Kutai Kartanegara Regency as part of the archipelago's capital city, which requires synergy between the Kutai Kartanegara Tourism Office Government so that it still exists and is not eroded by developments with the role of Tourism Ambassadors as an organization that is able to help the younger generation, especially high school students as the next tourism actors to be more aware of regional potential through Tourism Awareness Socialization activities. In Organizational Communication, of course, cooperation and synergy are the keys to achieving a goal with various stages initiated. In this research, the researcher wants to focus on the Role of the Kutai Kartanegara Tourism Ambassador in Tourism Awareness Socialization Activities for High School Students. Based on the above, the researcher aims to find out how the role of the Kutai Kartanegara Tourism Ambassador in synergy with the government to increase awareness of regional tourism potential. This research will be conducted using qualitative methods with a case study approach and with a constructivism paradigm. Researchers consider it important to conduct scientific research in the form of a thesis